The Effectiveness of Music Therapy on Reducing Anxiety Levels in Maternity Mothers - Nela Ardila; Omega DR Tahun (Proceedings of the International Conference on Nursing and Health Sciences, 2023)
Anxiety during labor can be a comorbidity and lead to low birth weight, preterm or preterm labor, hypertension and an increased risk of asthma. The effects of music therapy have been studied and promise a decrease in anxiety levels. The purpose of this study was to analyze the effect of Mozart's classical music therapy on the anxiety level of maternity mothers at UPT Puskesmas Ciomas. Research design quasy experimental one group pre-post test. 31 maternity mothers who entered the latent phase 1 to the end of the active phase 1 during the study period were studied with the HARS instrument. Bivariate analysis will be performed with an independent t test. Based on bivariate analysis, it was reported that Mozart's classical music therapy could reduce anxiety levels and was statistically significant (p value 0.012 < 0.05). Mozart's classical music therapy can calm and reduce anxiety levels in maternity mothers.